Local Wisdom-Based E-Book Media to Improve Elementary School Students' Social Skills - Nurhadifah Amaliyah; Musdalifa; Ismail Rahman; Perawati Bte Abustang; Waddi Fatimah (The Indonesian Institute of Science and Technology Research, 2026)
This study aims to examine the effectiveness of local wisdom-based e-book media in improving the social skills of elementary school students. The e-book integrates Makassar cultural values, such as tudang sipulung, which emphasizes deliberation and collective problem-solving, and abbulo sibatang, which reflects solidarity and mutual assistance. Using a quantitative approach with a pre-experimental design, the study was conducted at UPT SPF SD Inpres Manggala. The participants consisted of 38 fourth-grade students selected through purposive sampling. Data on students’ social skills were collected using structured instruments administered before and after the implementation of the e-book media. Data analysis was carried out using descriptive statistics and inferential analysis with SPSS Statistics 25 to examine changes in students’ social skills. The results of the hypothesis testing indicated a statistically significant improvement in students’ social skills after the use of the local wisdom-based e-book media (p < 0.05). These findings demonstrate that culturally contextualized digital learning media can effectively support the development of students’ social competencies. This study contributes to the field of elementary education by providing empirical evidence on the integration of local cultural values into digital learning media, highlighting its potential to strengthen social skills while fostering cultural identity in an engaging and meaningful learning environment.